Identité nationale et relations communautaires à travers l’œuvre poétique de Kóstas Montis - Alexandre Lapierre (Cahiers Balkaniques)
Costas Montis is a leading writer of the Greek-Cypriot poetry of the 20th century, one of the most well-known and celebrated; his poetry, as the works of others Cypriot poets, reflects the passions and tragedies of the island, the height of the fight for independency, the pain and anger, the hope for reunification and the highlighting of a common identity between Greek and Turks Cypriots.